1993
DOI: 10.1016/s0006-3495(93)81561-3
|View full text |Cite
|
Sign up to set email alerts
|

Saturation transfer electron parametric resonance of an indane-dione spin-label. Calibration with hemoglobin and application to myosin rotational dynamics

Abstract: We have used a recently synthesized indane-dione spin label (2-[-oxyl-2,2,5,5-tetramethyl-3-pyrrolin-3-yl)methenyl]in dane-1,3-dione (InVSL) to study the rotational dynamics of myosin, with saturation-transfer electron paramagnetic resonance (ST-EPR). To determine effective rotational correlation times (tau effr) from InVSL spectra, reference spectra corresponding to known correlation times (tau r) were obtained from InVSL-hemoglobin undergoing isotropic rotational motion in aqueous glycerol solutions. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 37 publications
5
50
0
Order By: Relevance
“…However, complementary experiments with SHi-bound maleimide spin labels (MSL), indane-dione spin labels (InVSL), or phosphorescent dyes, which bind rigidly to myosin heads even in the presence of ATP and report the global behavior of myosin heads, can be compared directly with this study. In agreement with the present study on IASL-fibers, the EPR spectrum of SHlbound MSL (Thomas and Cooke, 1980;Fajer et al, 1990a,b) or InVSL (Roopnarine et al, 1993;Roopnarine solved. As the apparent equilibrium constant for ATP hy- Intermediates and step numbers are defined as in Scheme 1, except that ATP and ADP are abbreviated as T and D, respectively.…”
Section: Relationship To Other Studiessupporting
confidence: 93%
See 1 more Smart Citation
“…However, complementary experiments with SHi-bound maleimide spin labels (MSL), indane-dione spin labels (InVSL), or phosphorescent dyes, which bind rigidly to myosin heads even in the presence of ATP and report the global behavior of myosin heads, can be compared directly with this study. In agreement with the present study on IASL-fibers, the EPR spectrum of SHlbound MSL (Thomas and Cooke, 1980;Fajer et al, 1990a,b) or InVSL (Roopnarine et al, 1993;Roopnarine solved. As the apparent equilibrium constant for ATP hy- Intermediates and step numbers are defined as in Scheme 1, except that ATP and ADP are abbreviated as T and D, respectively.…”
Section: Relationship To Other Studiessupporting
confidence: 93%
“…This leaves open the possibility that some heads contain additional spin labels attached to sites that do not affect the ATPase activity. However, the number of spin labels bound per myosin head (determined as described by Roopnarine et al, 1993) was found to be 0.68 ± 0.08, precisely matching the fraction of heads with inhibited K/EDTA-ATPase, implying that virtually all of the spin labels are bound to SHi, to the exclusion of all other sites in the fiber (Matta and Thomas, 1992;Matta, 1994). Fig.…”
Section: Specificity Of Spin Labelingmentioning
confidence: 85%
“…Thus, the InVSL label is immobilized both on the nanosecond time scale of EPR and on the millisecond time scale of ST-EPR experiments, and therefore can be used to study the dynamics of the regulatory domain. The InVSL was previously shown to be rigidly attached to Cys-707 of the catalytic domain using the same criteria (18). Mobility in Myosin Filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Myofibrils were prepared from fiber bundles and assayed for protein concentration as described by Roopnarine and Thomas (1994b). High-salt (K/EDTAand Ca/K-) ATPase assays were performed on myofibrils as described by Roopnarine et al (1993). The fraction of heads labeled at SHI and/or SH2 (fsH) was determined to be 0.63 ± 0.05 as described in Roopnarine and Thomas (1994b), from the fractional inhibition of the K/EDTA-ATPase activity of the labeled sample (KL) relative to the unlabeled controls (KUL):fsH = (KUL -KL)/(KUL -K.), where K., the activity of maximally labeled myosin heads in myofibrils, was determined to be 0.04 ,imol Pi/mg/min (Roopnarine and Thomas, 1994b).…”
Section: Preparations and Assaysmentioning
confidence: 99%
“…We have recently shown that this need is met by a newly synthesized indane dione spin label, designated InVSL (2-[-oxyl-2,2,5,5-tetramethyl-3-pyrrolin-3-yl)methenyl]indane-1,3-dione) ( Roopnarine and Thomas, 1994b). InVSL is covalently and rigidly immobilized on myosin, so that it reports the global rotation of myosin heads (Roopnarine et al, 1993), and it binds to muscle fibers in rigor with its principal axis almost precisely parallel to the fiber axis, making its EPR spectra directly and unambiguously sensitive to axial rotations of the myosin heads (Roopnarine and Thomas, 1994b). Therefore, in the present study, we have used conventional EPR spectroscopy of InVSL-labeled muscle fibers to study the orientation of myosin heads in rigor, relaxation, and isometric contraction.…”
Section: Introductionmentioning
confidence: 99%